O/F co-doped CNTs promoted graphite felt gas diffusion cathode for highly efficient and durable H2O2 evolution without aeration. (20th March 2022) - Gu, Ying-ying; Fu, Haojie; Huang, Ziwei; Lin, Rundong; Wu, Zuzhao; Li, Mingyue; Cui, Yafei; Fu, Rongbing; Wang, Shaobin
Abstract: Electrocatalytic reduction of O2 is an environmentally friendly method for H2 O2 production. Design and fabrication of efficient non-metallic electrocatalytic gas diffusion cathode (GDC) with strong durability is highly desirable. Carbon nanotubes (CNTs) is a promising electrocatalytic material for 2-electron O2 reduction but with unsatisfying electrocatalytic activity and stability. Hetero-atom doping of CNTs has been proved to promote its electrocatalytic selectivity for H2 O2 generation, but the electrocatalytic performance of CNTs co-doped with two hetero-atoms and its synergy mechanisms need further investigation. Herein, O or F mono-doped and O/F co-doped CNTs with different O/F ratios were developed through one-step acidification and then used as the electrocatalysts on the graphite felt (GF) GDC for H2 O2 generation. The electrocatalytic activity was greatly improved by the synergetic effects of O/F-containing functional groups on the surface of CNTs. The GF/CNTs-1:1 cathode with the highest contents of COOH and CFX (X ≥ 2) was found to be most efficient in H2 O2 electrogeneration at a wide pH range of 1–9. Further, with coating of polytetrafluoroethylene (PTFE) film, the GF/CNTs-1:1/PTFE-30 GDC exhibited extremely high activity and superior stability in 15 cycles without aeration, giving the maximum H2 O2 yield of 263.2 mg·L −1 in 1 h with little decline rate. The present study provides opportunities for developing highly efficient, cost effective, and durable metal-free electrocatalysts for H2 O2 evolution. Graphical abstract: Image 1 Highlights: A novel O/F co-doped CNTs promoted graphite felt GDC was prepared for H2 O2 evolution. The GF/CNTs-1:1 cathode had the highest electrocatalytic activity in a wide pH range 1–9. The composite GF/CNTs-1:1/PEFE-30 GDC exhibited excellent performance (H2 O2 yield reaching 263.2 mg L −1 at 1 h without aeration) and superior stability after 15 runs. Increased number and synergetic effects of COOH and CFX (X ≥ 2) mainly contributed to the high electrocatalytic activity of the GDC.